Understanding the performance improvement mechanism of Ti/steel clad plates fabricated by double-layered hot rolling - Yue Wu; Renhao Wu; Haiming Zhang; Tao Wang; Qingxue Huang; Hyoung Seop Kim (Journal of Materials Research and Technology)
Developing high-performance Ti/steel clad plates is crucial for applications demanding superior mechanical properties and cost efficiency. In this study, we fabricated Ti/steel clad plates via hot rolling using symmetrical assembly (SA) and double-layer assembly (DA) methods. Through comprehensive microstructure characterizations and finite element method (FEM) analysis, we elucidated the influence of assembly configurations on microstructural evolution and mechanical properties. The results show that the DA method achieved higher bonding strength with a single rolling pass than the SA method with two passes, indicating a more efficient bonding process. In the SA method, the symmetric geometry concentrated the overall deformation of the clad plates on the Ti side during rolling, leading to interfacial sliding and accelerating the thinning of the Ti side thickness. This degraded the interfacial bonding strength and triggered geometric dynamic recrystallization (GDRX) on the Ti side. In contrast, the asymmetric DA geometry promoted shear deformation in the steel side, ensuring comparable thickness reduction in both Ti and steel, thereby enhancing the interface bonding strength and deformation coordination between the components. Additionally, direct Ti-roller contact in DA not only improved the surface finish but also reduced the difference in deformation resistance between Ti and steel plates through heat transfer. The continuous dynamic recrystallization (CDRX) in the Ti side of the DA samples, produced finer grains and higher geometric necessary dislocation (GND) density. The combined effects of higher work hardening in the matrix and robust interfacial bonding contribute to the enhanced tensile properties observed in DA clad plates. Our findings underscore the potential of the DA approach, coupled with hot rolling, to produce Ti/steel clad plates with exceptional mechanical properties, providing valuable insights for optimizing bimetallic composite manufacturing processes.